Authenticity of architecture, place attachment, identity and support for sustainable tourism in world heritage cities - Francisco Orgaz-Agüera; Miguel PUIG-CABRERA; Salvador MORAL-CUADRA; Cándida María DOMÍNGUEZVALERIO (Tourism and Hospitality Management, 2025)
Purpose - This study analyses the relationships between perceived architectural authenticity, localised identity, place attachment and support for sustainable tourism at a World Heritage Site. Methodology/Design/Approach - A quantitative methodology is developed through questionnaires applied to residents in the Colonial Zone of Santo Domingo, in the Dominican Republic. 509 valid responses were obtained and the analysis used structural equation models (PLS-SEM). Findings - The results show that perceived architectural authenticity significantly influences the residents’ place attachment and localised identity. These, in turn, impact their support for the creation of sustainable tourism initiatives at heritage sites. Specifically, architectural authenticity enhances the residents’ connection to their community and cultural identity, fostering a supportive attitude toward the sustainable tourism practices that preserve cultural heritage. Originality of the research - The findings suggest that architectural authenticity is relevant when it comes to strengthening the community ties and cultural identity among the residents of World Heritage Sites. A model is presented where architectural authenticity is analyzed and variables are integrated that analyze how it influences support for sustainable tourism. This model, unlike similar models, offers updated data after the pandemic.